Neoadjuvant treatment in advanced renal cell carcinoma: current situation and future perspectives. Issue 12 (December 2012) - Timsit, Marc-Olivier; Albiges, Laurence; Méjean, Arnaud; Escudier, Bernard
Neoadjuvant approaches in renal cell carcinoma are currently under investigation, following the demonstration of targeted therapy efficacy in the metastatic setting. It raises the issues of downsizing locally advanced or nonresectable tumor and offering organ-sparing surgery, saety and its potential role in early micrometastatic disease. Relevant studies of the neoadjuvant setting in renal cell carcinoma with targeted therapies were identified from the literature, clinical trial databases and conference abstracts. To date, a neoadjuvant approach appears feasible in terms of saety. Currently available drugs do not achieve major tumor downsizing with primary tumor diameters response rate of 10%. Neoadjuvants should only be considered in clinical trials or as a litmus test in locally advanced patients.